2012
DOI: 10.1017/s0950268812000568
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the true incidence of campylobacteriosis and salmonellosis in the European Union, 2009

Abstract: We estimated the true incidence of campylobacteriosis and salmonellosis in the European Union (EU) in 2009. The estimate was based on disease risks of returning Swedish travellers, averaged over the years 2005-2009, and anchored to a Dutch population-based study on incidence and aetiology of gastroenteritis. For the 27 EU member states the incidence of campylobacteriosis was about 9·2 (95% CI 2·8-23) million cases, while the incidence of salmonellosis was 6·2 (95% CI 1·0-19) million cases. Only 1/47 (95% CI 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
143
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(152 citation statements)
references
References 10 publications
2
143
0
6
Order By: Relevance
“…The most current evaluation of the epidemiology of campylobacteriosis in 27 European Union (EU) state members indicated the incidences of Campylobacter infections to range from 29.9 to 13,500 per 100,000 population in 2009 (with the lowest incidences in Finland and Sweden and the highest in Bul-garia) (46). Overall, this equated to 9.2 million cases, compared to 6.2 million cases of salmonellosis, in 2009 (46). A United Kingdom-wide study conducted over the period from April 2008 to August 2009 identified Campylobacter species as the most common bacterial pathogens in cases of gastroenteritis (47).…”
Section: Epidemiologymentioning
confidence: 99%
“…The most current evaluation of the epidemiology of campylobacteriosis in 27 European Union (EU) state members indicated the incidences of Campylobacter infections to range from 29.9 to 13,500 per 100,000 population in 2009 (with the lowest incidences in Finland and Sweden and the highest in Bul-garia) (46). Overall, this equated to 9.2 million cases, compared to 6.2 million cases of salmonellosis, in 2009 (46). A United Kingdom-wide study conducted over the period from April 2008 to August 2009 identified Campylobacter species as the most common bacterial pathogens in cases of gastroenteritis (47).…”
Section: Epidemiologymentioning
confidence: 99%
“…The potential benefit of an algorithm-based surveillance can be appreciated in the light of the relatively low number of reported Salmonella outbreaks in Israel, with only a single outbreak recognized in 2010 (31), while our analysis estimated that each year in Israel there are on average 23 potential outbreaks. If one takes into account the EU multiplier for the ratio of underdiagnosis of 58 for every laboratory-confirmed case (32), it is likely that the actual number of outbreaks in the community is even higher. Statistical surveillance methods such as the Farrington algorithm provide an economical, efficient, and valid tool for early detection of potential outbreaks that require further epidemiological investigation and confirmation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore countryspecific MFs should be used if possible [14,64,65]. The MFs estimated in this paper are the only ones available based on Swedish data, and these are therefore considered to be the most accurate estimates available.…”
Section: Discussionmentioning
confidence: 99%